2007
DOI: 10.5014/ajot.61.1.53
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition and Integration of Evidence-Based Practice Concepts by Occupational Therapy Students

Abstract: This article describes the ways in which master's of occupational therapy students across one professional curriculum expressed their learning of evidence-based practice (EBP). Through qualitative case methodology and focus group interviews, the student participants' perceptions of EBP were examined across varying levels of academic and clinical experiences. The present findings support the relevance of clinically based activity, particularly fieldwork experiences, along with discussion-based learning for deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 32 publications
(44 reference statements)
3
39
0
Order By: Relevance
“…The findings suggest that overall, students’ attitudes towards EBP were moderately positive, which is consistent with the findings from other studies [18, 22, 23] though there is room for improvement. Students appear to value EBP particularly as it enhances the profession’s credibility.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings suggest that overall, students’ attitudes towards EBP were moderately positive, which is consistent with the findings from other studies [18, 22, 23] though there is room for improvement. Students appear to value EBP particularly as it enhances the profession’s credibility.…”
Section: Discussionsupporting
confidence: 90%
“…A small study on final year OT students ( n  = 86) in Ireland, found that learners understand what EBP entails and are willing to use this approach to inform practice [22]. A qualitative study in the US showed that graduates generally hold positive attitudes toward EBP, view it as patient-centered, as embodying best practices, and as holding promise for the future of the profession [23]. A retrospective cohort study used a survey to explore master’s entry-level (MEL) and bachelor entry-level (BEL) graduates’ reasons for seeking and using information in their practice, the type of information they need most, how they search for it and how the information is used in clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Two experts in qualitative research not involved in the EBP educational pathway conducted the focus groups at the end of the academic year (after completion of formal courses and internships). The outline of the focus group was based on previous research (Ilic and Forbes, 2010;Stube and Jedlicka, 2007) and on a consensus process within the research team. Key questions explored were: the students' experience of the educational pathway; acceptance or rejection of EBP; the consistency of EBP in theory and practice; the importance of EBP for clinical practice; the feasibility of the different steps; and the barriers and facilitators.…”
Section: Perceptions and Attitudesmentioning
confidence: 99%
“…While Stronge and Cahill (2012) and Stube and Jedlicka (2007) examined the relationship of the student and fieldwork educator from the student's perspective, Thomas and Law (2014) examined the OT practitioner's perspective. They surveyed 1,800 Canadian occupational therapists working with children or older adults to determine supports for EBP and attitudes toward these supports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tying together the academic and clinical settings, Stube and Jedlicka (2007) used focus groups to learn more about OT students' perceptions of EBP in the classroom and during fieldwork. The students indicated that having positive role models for using EBP was important, and that their relationship with their fieldwork educator helped them learn to apply the principles of EBP (Stube & Jedlicka, 2007). There is a current lack of evidence available to determine if students are observing EBP clinically in the United States.…”
Section: Literature Reviewmentioning
confidence: 99%